Performance of High Strength Fiber Reinforced Mortar Made with Ceramic Powder, Metakaolin, and Magnetized Water - Osama Youssf; Khalid A. Eltawil; Mohamed M. Yousry Elshikh; Mostafa M. Keshta (Infrastructures)
In recent years, there has been a notable concern about the production of cementitious composites due to its high cement consumption and the corresponding carbon footprint. This has led to significant progress within the construction sector in integrating various waste materials as cement alternatives into cementitious composites. In this study, a sustainable high strength fiber reinforced mortar (HS-FRM) was designed with ceramic powder (CP) and metakaolin (MK) materials as partial replacements of the conventional HS-FRM by up to 80%. Magnetized water (MW) was used in the proposed HS-FRM as mixing water and replaced the normal tap water (TW) for producing a more sustainable and higher strength cementitious product. The HS-FRM was cured using four different curing methods, namely, tap water, seawater, air, and sunlight. Fresh, mechanical, durability, and microstructure characteristics were measured and analyzed for the proposed HS-FRM. The results showed that CP can enhance the slump of HS-FRM by up to 50% (achieved at 40% CP), while MK showed the same or less slump (by up to 33%) than that of the conventional HS-FRM. Using up to 80% of either CP or MK in the HS-FRM continuously decreased its 28-day compressive strength by up to 78% or 83%, respectively. The HS-FRM cured in tap water exhibited the highest compressive strength compared to the other curing conditions. The use of MW improved the workability of the HS-FRM by up to 225% and the compressive strength by up to 13%. The microstructure analyses interpreted the reported variation in the HS-FRM compressive strength and showed that using MW in the HS-FRM revealed a dense structure with an adequate bond between the fiber and the matrix with a relatively low number of micro-cracks and pores compared when using TW. The XRD analysis showed higher peaks of Q, C, and L with the presence of MW compared to mixtures made with TW.